Penicillin allergy evaluation; Experience from Clinic of allergology and immunology, Clinical Center of Serbia - Kusić, Nataša S; Tomić-Spirić, Vesna (Medicinski podmladak, 2018)
Introduction: Beta(β)-lactam antibiotics are one of the most prescribed medical drugs worldwide. The incidence of self-reported penicillin allergy ranges from 1 to 10 percent. Patients with registered allergy on β -lactam antibiotics are treated with drugs of second choice which are usually more toxic and more expensive. Aim: The aim of this study was to exam the prevalence of penicillin allergy and correlation of clinical, laboratory and socio-demographic characteristic of patients with and without hypersensitivity to penicillin which were available in medical records. Material and methods: This retrospective, descriptive study included consecutive patients, which were treated in  Clinic of Allergology and Immunology, Clinical Center of Serbia (CCS), in the period between the years 2010-2015. Anamnestic data of patients with self-reported allergic reaction to penicilin and the rest of β-lactam antibiotics were used, as well as results of in vivo and in vitro tests. Results: 81 patients were evaluated in the study, of which 59 (72.8%) were females. The average age of patients was 41.7±16.47 years. Adverse effects to penicillin were reported by 70/81 (86.4%) tested patients. In accordance with other studies, the most common initial symptoms were rash (exanthema) and angioedema. None of the 70 patients with self-reporetd allergic reaction to penicillin had positive in vitro tests. Total number of patients with positive in vivo tests is 2/81 (2.5%) Conclusion: It is well-known that about 90% of patients with reported presence of allergy to penicillin are not allergic, so they can be safely treated with this group of drugs in therapeutic purpose, what was also confirmed in our study. Earlier studies have shown that hypersensitivity to cephalosporins is more frequent in patients which are labeled as hypersensitive to penicillin. An exact evaluation of cross-reactivity between penicillins and cephalosporins was not possible in our study due to the small number of patients.